Functional Implications of RNA Splicing for Human Long Intergenic Noncoding RNAs. (January 2014) - Chen, Feng-Chi; Pan, Chia-Lin; Lin, Hsuan-Yu
Long intergenic noncoding RNAs (lincRNAs) have been suggested as playing important roles in human gene regulation. The majority of annotated human lincRNAs include multiple exons and are alternatively spliced. However, the connections between alternative RNA splicing (AS) and the functions/regulations of lincRNAs have remained elusive. In this study, we compared the sequence evolution and biological features between single-exonic lincRNAs and multi-exonic lincRNAs (SELs and MELs, respectively) that were present only in the hominoids (hominoid-specific) or conserved in primates (primate-conserved). The MEL exons were further classified into alternatively spliced exons (ASEs) and constitutively spliced exons (CSEs) for evolutionary analyses. Our results indicate that SELs and MELs differed significantly from each other. Firstly, in hominoid-specific lincRNAs, MELs (both CSEs and ASEs) evolved slightly more rapidly than SELs, which evolved approximately at the neutral rate. In primate-conserved lincRNAs, SELs and ASEs evolved slightly more slowly than CSEs and neutral sequences. The evolutionary path of hominid-specific lincRNAs thus seemed to have diverged from that of their more ancestral counterparts. Secondly, both of the exons and transcripts of SELs were significantly longer than those of MELs, and this was probably because SEL transcripts were more resistant to RNA splicing than MELs. Thirdly, SELs were physically closer to coding genes than MELs. Fourthly, SELs were more widely expressed in human tissues than MELs. These results suggested that SELs and MELs represented two biologically distinct groups of genes. In addition, the SEL–MEL and ASE–CSE differences implied that splicing might be important for the functionality or regulations of lincRNAs in primates.